Carbon Accountability in Indonesia’s State-Owned Assets Management - Rasyidi, Mohammad Amin; Setiya, Tanda (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality: This study is among the first to introduce an Environmentally Extended Input-Output (EE-IO) framework to quantify the carbon externalities of state-owned assets (BMN) management in Indonesia. This area has received limited empirical attention. Research Objectives: The study aims to systematically measure direct and indirect carbon emissions associated with BMN utilization and assess their implications for public asset governance. Research Methods: An EE-IO model is constructed using Indonesia’s 2016 input-output table, sectoral emission intensities, and audited government electricity expenditure data to estimate emission multipliers and carbon impacts. Empirical Results: The Electricity and Gas Supply sector exhibits the highest emission multiplier (4,919.05 tons CO₂ per billion Rupiah). Electricity-related BMN expenditure is estimated to generate 28.4 million tons of CO₂, revealing a substantial but previously under-recognized source of environmental burden. Implications: The findings support emission-informed budgeting, emission-based performance indicators, and the integration of carbon accountability into public asset management. JEL Classification: Q56, H54, D57, H83